Clinical Predictors for Optimal Forward Elevation in Primary Reverse Total Shoulder Arthroplasty. (February 2019) - Sollaccio, David R; King, Joseph J; Struk, Aimee; Farmer, Kevin W; Wright, Thomas W
Background: Few studies in the literature analyze clinical factors associated with superoptimal and suboptimal forward elevation in primary reverse total shoulder arthroplasty (RTSA). We investigate the functional outcome stratified by shoulder elevation 12 months after primary RTSA and its correlation with selected clinical patient factors. Methods: We analyzed prospectively collected data within a comprehensive surgical database on patients who had undergone primary RTSA between June 2004 and June 2013. Two hundred eighty-six shoulders were stratified into 2 groups: group I for shoulders that had achieved at least 145° of active forward elevation 12 months postoperatively (90th percentile of active forward elevation, 29 shoulders) and group II for shoulders that never achieved at least 90° of active forward elevation 12 months postoperatively (10th percentile of active forward elevation, 28 shoulders). Statistical analysis associated independent clinical variables with postoperative motion using univariate analysis followed by logistic regression. Results: Active shoulder elevation of at least 90° was achieved 12 months postoperatively in 259 subjects (90%). Upon comparison with group II (<90° elevation), subjects in group I (≥145° elevation) were found to have improved postoperative active elevation and relatively younger age, lower American Society of Anesthesiologists score, increased preoperative active elevation, increased shoulder strength, increased passive elevation, decreased elevation lag, increased active and passive external rotation, and improved validated outcome scores. When assessing significant preoperative variables, the only independent predictor of improved postoperative forward elevation was preoperative active forward elevation. Conclusion: These findings illuminate significant factors in the ability to achieve functional active shoulder elevation after primary RTSA. They may help surgeons appropriately counsel patients about anticipated functional prognosis following primary RTSA.